Structure of stratlingite and effect of hydration methodology on microstructure - Santacruz-Cruz, María Isabel; Gómez-de-la-Torre, María de los Ángeles; Álvarez-Pinazo, Gema; Cabeza-Díaz, Aurelio; Cuesta-García, Ana María; Sanz, Jesus; García-Aranda, Miguel Ángel (ICE publishing, 2015)
Stratlingite, Ca4Al2(OH)12[AlSi(OH)8]2•2H2O, is an AFm phase which appears as hydration product of aluminum-rich cements. These binders may be calcium aluminate cements, calcium sulfoaluminate cements and also Belite Calcium Sulfo-Aluminate (BCSA) cements. The structure of stratlingite is known from single crystal studies of tiny minerals but their bulk formation, crystal structure and microstructure of powders is poorly understood. Here, we report the synthesis of stratlingite and a complete structural and microstructural characterization by synchrotron X-ray powder diffraction, nuclear magnetic resonance, scanning electron microscopy and thermal analyses. The structural and microstructural models have important implications for a correct quantitative phase analysis of stratlingite in cement pastes (for instance, in pastes of BCSA cements). The microstructure of stratlingite formed in cement pastes is highly dependent on the hydration conditions. In BCSA pastes, the (003) line position of stratlingite appears slightly shifted towards higher diffracting angles (lower inter-layered distance) after stopping hydration compared to that of a similar phase present in a paste analyzed without stopping hydration. This is related to dehydration and disorder. This shift and peak broadening is even larger when the paste has suffered partial dehydration during curing (apart from stopping hydration). A microstructural study is reported
Keywords: Rietveld, Método de; Cemento; Stratlingite; Structure; Microstructure; Synchrotron X-ray powder diffraction; Rietveld refinement; Belite calcium sulfoaluminate cements